2006
DOI: 10.1242/jcs.02941
|View full text |Cite
|
Sign up to set email alerts
|

PLD1 and ERK2 regulate cytosolic lipid droplet formation

Abstract: We have previously uncovered roles for phospholipase D (PLD) and an unknown cytosolic protein in the formation of cytosolic lipid droplets using a cell-free system. In this report, PLD1 has been identified as the relevant isoform, and extracellular signal-regulated kinase 2 (ERK2) as the cytosolic protein. Increased expression of PLD1 increased lipid droplet formation whereas knockdown of PLD1 using siRNA was inhibitory. A role for ERK2 in basal lipid droplet formation was revealed by overexpression or microin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
135
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(144 citation statements)
references
References 50 publications
7
135
0
2
Order By: Relevance
“…Our findings indicate that CCR2-driven lipid body biogenesis triggered by MCP-1 is dependent on downstream activation of PI3K and ERK1/2 kinases. Accordingly, activation of ERK 1/2 and PI3K in response to CC chemokines has been shown to participate in the regulated activation of lipid body biogenesis in other cell systems (25,32), as well as in other MCP-1-induced leukocyte functions (26,33). The specific isoform(s) involved in MCP-1-induced lipid body biogenesis are presently unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings indicate that CCR2-driven lipid body biogenesis triggered by MCP-1 is dependent on downstream activation of PI3K and ERK1/2 kinases. Accordingly, activation of ERK 1/2 and PI3K in response to CC chemokines has been shown to participate in the regulated activation of lipid body biogenesis in other cell systems (25,32), as well as in other MCP-1-induced leukocyte functions (26,33). The specific isoform(s) involved in MCP-1-induced lipid body biogenesis are presently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using NIH 3T3 cells stimulated with insulin have established that dynein, a microtubule motor, has a central role in the growth of lipid bodies by fusing them (36). Dynein required phosphorylation, performed by the MAPK ERK2, to interact with its cargos, such as lipid bodies and may potentially control lipid body assembly by providing the structural conditions required to let the lipid body arise from the ER membrane (32). In agreement with this hypothesis, here we showed that lipid body assembly triggered by activation of CCR2 by MCP-1 depends on activities of both ERK 1/2 kinases and the microtubular system of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In neuronal synapses, α-synuclein is involved in regulation of synaptic vesicle fusion with the cell membrane by promoting the assembly of SNARE complexes (11). In adipocytes, SNARE complexes have been implicated in lipid droplet formation and growth by fusion between neutral TAG packaged within amphipathic lipoproteins and the lipid droplet phospholipid monolayer (12)(13)(14)(15). To determine whether γ-synuclein may regulate the efficiency of this fusion mechanism, we quantified the assembled SNARE complexes in epididymal WAT lysates by measuring the amount of VAMP-4 (vSNARE) that coimmunoprecipitated with syntaxin-5 (tSNARE).…”
Section: γ-Synuclein Promotes Assembly Of Snare Complexes In Wat Andmentioning
confidence: 99%
“…The involvement of microtubules in the transport of oil drops is well established in animal cells (Zehmer et al 2009 and references therein). It has been showed that the ability of oil drops to form and grow in size (Andersson et al 2006) and their rapid movement in the cytoplasm (Gross et al 2000) is dependent on microtubules. So, we suggest that the more intense marking for microtubules in cells secreting abundant lipophilic compounds in H. villosa may be associated with the involvement of these elements in the intracellular transport of oil bodies.…”
Section: Discussionmentioning
confidence: 99%